Dysregulation of serum miR-361-5p serves as a biomarker to predict disease onset and short-term prognosis in acute coronary syndrome patients - Wenqing Zhang; Guannan Chang; Liya Cao; Gang Ding (BMC Cardiovascular Disorders, 2021)
Abstract Background Serum microRNAs (miRNAs) have been used as novel biomarkers for various diseases, including acute coronary syndrome (ACS). This study aimed to investigate the expression and clinical significance of microRNA-361-5p (miR-361-5p) in patients with ACS. Methods This study included 118 ACS patients, 78 patients with stable coronary heart disease (SCHD) and 66 healthy controls. MiR-361-5p expression was measured by qRT-PCR. The diagnostic value of miR-361-5p was evaluated by the ROC analysis. A 30-day follow-up was performed for the patients from hospitalization, and Kaplan–Meier curves and logistics analysis were used to evaluate the ability of miR-361-5p to predict the occurrence of major adverse cardiac events (MACE). ELISA kits were used to detect the levels of endothelial dysfunction (ED) markers, including vascular cell adhesion molecule 1 (VCAM-1), intercellular adhesion molecule 1 (ICAM-1) and E-selectin. Results The expression of miR-361-5p was significantly increased in patients with SCHD and ACS, and positively correlated with Gensini scores. Serum miR-361-5p expression had a high diagnostic accuracy for distinguishing ACS from health controls and SCHD patients. ACS patients with high expression of miR-361-5p had a higher probability of developing MACE. MiR-361-5p expression was an independent risk factor for the occurrence of MACE in ACS patients, and was positively correlated with the levels of VCAM-1, ICAM-1 and E-selectin. Conclusion All data indicated that miR-361-5p expression was significantly increased in ACS patients. Aberrant miR-361-5p expression in ACS might be a candidate biomarker for ACS diagnosis and the the prediction of MACE onset.